Grain Size Effects in Mn-Modified 0.67BiFeO3–0.33BaTiO3 Ceramics - Yue, Yajun; Xu, Xinzhao; Zhang, Man; Yan, Zhongna; Koval, Vladimir; Whiteley, Richard M; Zhang, Dou; Palma, Matteo; Abrahams, Isaac; Yan, Haixue (ACS applied materials & interfaces, 2021)
Grain size can have significant effects on the properties of electroceramics for dielectric, piezoelectric, and ferroelectric applications. Here, we systematically investigate the effect of grain size on the structure and properties of Mn-modified 0.67BiFeO3–0.33BaTiO3 ceramics, an important lead-free piezoelectric ceramic that exhibits both a high piezoelectric coefficient and a high Curie point. Ceramics with average grain sizes ranging from 0.46 to 6.85 μm were prepared using conventional and spark plasma sintering. It was found that the morphotropic phase boundary compositions are composed of two polar structures, rhombohedral and tetragonal, with DC poling inducing an increase in the fraction of the rhombohedral phase. All ceramics show relaxor behavior and their freezing temperature moves to higher temperatures with increasing grain size, although their Burns temperature is independent of grain size. In fine-grained ceramics, which show pronounced relaxor behavior, significant grain size dependency is seen in dielectric, piezoelectric, and ferroelectric properties, which is attributed to the presence of single ferroelectric domains and high concentrations of polar nanoregions. In coarse-grained ceramics, a critical grain size of 2.83 μm yields the highest dielectric permittivity at room temperature, with the piezoelectric coefficient plateauing at this grain size, which can be attributed to the contribution of both polar nanoregions and high domain wall density.